Effectiveness of rambutan honey toothpaste on IL-6 gene expression during acute inflammatory phase of gingivitis in a Wistar rat model: an experimental study - Putri, Reika Yulia; Yuslianti, Euis Reni; Prayudha, Ramadhita Paramananda; Widowati, Wahyu; Noviani, Indah Yuri (Universitas Padjadjaran, 2026)
Introduction: Gingivitis is a reversible form of periodontal disease characterized by gingival inflammation due to dental plaque accumulation and increased inflammatory mediators such as IL-6. Rambutan honey (Nephelium lappaceum) contains bioactive compounds with potential as natural anti-inflammatory agents. This study aimed to analyze the effectiveness of rambutan honey toothpaste on IL-6 gene expression during acute inflammatory phase of gingivitis in a Wistar rat model. Method: This study used a true experimental design with a post-test only control group design. A total of 30 male Wistar rats were randomly divided into three groups: negative control (toothpaste base/NC), positive control (commercial herbal toothpaste/PC), and treatment (rambutan honey/TPRH). The gingivitis rat model was established using a ligature technique with silk thread and inoculation of Porphyromonas gingivalis and Streptococcus mutans. Treatment was administered twice daily for seven days, and gene expression was evaluated on days 0, 3, 5, and 7 using qRT-PCR. Data were analyzed using ANOVA and post hoc Tukey tests (p<0.05). Result: The rambutan honey toothpaste group showed a decreasing pattern of IL-6 expression compared to the base and commercial toothpaste groups, particularly on day 3 (p=0.038). These findings suggest that rambutan honey toothpaste may reduce IL-6 expression. This effect may be related to the presence of flavonoid and phenolic compounds in rambutan honey, which have been associated with anti-inflammatory activity. Conclusion: Rambutan honey toothpaste was associated with reduced IL-6 gene expression during the early acute inflammatory phase of experimental gingivitis in Wistar rats, indicating a potential anti-inflammatory effect at the molecular level. Further studies, including clinical, histological, and protein-level assessments, are needed to confirm its relevance in gingival healing.